The cost of adopting a complete system of public prosecution in England, as illustrated by the results of the working of the Scotch and Irish systems of public prosecution - Hancock, W. Neilson (Statistical and Social Inquiry Society of Ireland, 1879)
There are many indications that the extension to England of the system of Public Prosecution which has so long existed both in Scotland and Ireland is only a question of time. This assimilation of the laws of the United Kingdom was recommended by a Royal Commission so far back as 1844; it was recommended by a Parliamentary Committee in 1856 and by another Committee in 1870. Bills were introduced on the subject in the sessions of 1870, 1871, and 1872, with different names on them in the several years, but including Mr. Walpole, Viscount Sandon, Mr. Russell Gurney, Mr. Vernon Harcourt, Mr. Rathbone, and Mr. Eykyn. In 1873 a Bill was introduced by the Government. As an indication of the strength of feeling entertained on the subject, I may quote a few words from Mr. Walpole's speech on the 19th of June, 1872: ?It was really a disgrace?and he used the word advisedly?that England was the only country in the world where prosecutions for crime should be mostly left at the mercy of private individuals, who might or might not proceed with them as they thought fit?.
Read at the Section of Economic Science and Statistics of the British Association, at Plymouth, August, 1877
Keywords: English law reform; Public prosecution system; 314.15